2017
DOI: 10.1039/c6cp07142b
|View full text |Cite
|
Sign up to set email alerts
|

Reactive collisions for NO(2Π) + N(4S) at temperatures relevant to the hypersonic flight regime

Abstract: The NO(XΠ) + N(S) reaction which occurs entirely in the triplet manifold of NO is investigated using quasiclassical trajectories and quantum simulations. Fully-dimensional potential energy surfaces for the A' andA'' states are computed at the MRCI+Q level of theory and are represented using a reproducing kernel Hilbert space. The N-exchange and N-formation channels are followed by using the multi-state adiabatic reactive molecular dynamics method. Up to 5000 K these reactions occur predominantly on the NO A'' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 51 publications
(76 reference statements)
1
65
2
Order By: Relevance
“…Gas-phase reactive molecular dynamics simulations starting from an equilibrated ensemble of a statistically significant number of initial conditions, on the other hand, have recently been shown to provide molecular-level details into reactions relevant to atmospheric chemistry 28,29 and reactions in the hypersonic regime. 30,31 From an experimental perspective, the most precise data on reaction mechanisms and dynamics can be gained from gas-phase studies performed under single-collision conditions. As the progress in molecular-beam experiments allows the probing of ever-larger systems under precisely defined conditions, 32,33 the open questions pertaining to the mechanistic details of Diels-Alder reactions become an attractive target of study.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase reactive molecular dynamics simulations starting from an equilibrated ensemble of a statistically significant number of initial conditions, on the other hand, have recently been shown to provide molecular-level details into reactions relevant to atmospheric chemistry 28,29 and reactions in the hypersonic regime. 30,31 From an experimental perspective, the most precise data on reaction mechanisms and dynamics can be gained from gas-phase studies performed under single-collision conditions. As the progress in molecular-beam experiments allows the probing of ever-larger systems under precisely defined conditions, 32,33 the open questions pertaining to the mechanistic details of Diels-Alder reactions become an attractive target of study.…”
Section: Introductionmentioning
confidence: 99%
“…In Eq. 10, w j (x) is the normalized weight 35,42 which has also been used for mixing double many-body expansion PESs. 43 However, other mixing functions are possible such as a tangent hyperbolic 34,41 and thus, no physical significance should be attributed to the mixing function.…”
Section: Multi-state Mmptmentioning
confidence: 99%
“…This work focused on the scattering process and found that the fraction of NO deflected in the forward direction decreases with increasing collision energy. Complementary to this, RKHS‐interpolated PESs based on MRCI+Q calculations were used to determine rate coefficients for different reaction channels for temperatures up to 20,000 K (see Figure ; Reference ). From the QCT simulations the rates k ( T ) for 5,000 ≤ T ≤ 20,000 can be fit to an Arrhenius expression kexch()T=1.475×1010exp()20907.67/T and kform()T=1.712×1010exp()7423.430/T for the exchange and N 2 formation processes, respectively.…”
Section: Applicationsmentioning
confidence: 99%
“…For the related NO(X 2 Π) + N( 4 S) $ N 2 (X 1 Σ) + O( 3 P) reaction fully dimensional, global PESs have also been computed. [161][162][163] Based on CASPT2 calculations a many-body expansion was fitted and used for variational transition state calculations 162 and QCT simulations. 164 A more recent effort used a least-squares fit of permutationally invariant polynomials to dynamically scaled MRCI energies.…”
Section: Small Molecule Reactionsmentioning
confidence: 99%